Isolation of Endophytic Fungi in Rhizophora Apiculata Mangroves in Teluk Buo Mangrove Area, Bungus Teluk Kabung District, West Sumatra - Rury Trisa Utami; Delladari Mayefis; Hesti Marliza (Formosa Journal of Sustainable Research, 2023)
Endophytic fungi are microbes that live in plant tissues that are able to produce secondary metabolite compounds and have the potential to be antibacterial, antifungal and anticancer. Purpose: To isolate endophytic fungi on mangrove plants Rhizophora apiculata that can be used as antibiotics. Method: This study was conducted experimentally in the microbiology laboratory by isolating endophytic fungi in mangrove roots, after isolation followed by microscopic observations to identify the type of fungus that grew. Results: Based on the results of observation and identification, the endophytic fungal genus Penicilium sp was successfully isolated from the mangrove roots of Rhizophora apiculata. Conclusion: Penicilium sp is an endophytic fungus obtained from the roots of the mangrove Rhizophora apiculata